Island biodiversity hotspots are getting hotter: vulnerability of tree species to climate change in New Caledonia. (September 2016) - Pouteau, Robin; Birnbaum, Philippe
Abstract: Future patterns of biodiversity have been extensively explored to design conservation strategies in large continental hotspots. However, little research has focused on island hotspots, although limited opportunities to migrate and the inherent characteristics of island species are likely to cause sensitivity to rapid environmental changes. This study addresses the question of how climate change could affect species richness in New Caledonia, the world's smallest biodiversity hotspot. An individual species distribution model was built for 469 native tree species and projected according to nine climate change scenarios. Results indicated that the range size of 87–96% of species will have declined by 2070, 52–84% will lose at least half of their current range, and 0–15% will become extinct. Surprisingly, these predictions did not significantly exceed those for larger biodiversity hotspots. Underlying reasons may include an oceanic buffering effect that attenuates increases in air temperature, and the complex topography that generates micro-refugia. Major losses in local species richness were predicted to occur on ultramafic substrates and at mid-elevation. Loss on ultramafic substrates may stem from the number of ultramafic-specialist species that will lack a suitable climate on this specific substrate, while substrate-ubiquitous species are more likely to find refugia. Loss at mid-elevation could mirror a shift in optimum temperature-precipitation value, whose role in shaping the current pattern of diversity may have been overestimated by the models. Hopefully, these results will encourage further research to define the right mitigation and adaptation strategies on oceanic islands, where extinctions would contribute disproportionally to global biodiversity decline.